Выбор и эксплуатация редукторов на металлургических предприятиях: справочник - Ножненко А. В. Александр Владимирович; Данилов Л. И. Леонид Иванович; Головач О. Г. Олег Григорьевич; Иванов П. Ф. Петр Федорович; Елистратова Р. Т. Римма Теодоровна (Москва, Металлургия, 1983)
Авт. указаны на обороте тит. л.